COMPARATIVE ANALYSIS OF COGNITIVE ABILITIES STRESS TOLERANCE AND DECISION-MAKING PROCESS IN NOVICE AND EXPERIENCED ATHLETES - Donka, Dorottya Bianka; Balogh, László (Stadium - Hungarian Journal of Sport Sciences, 2021)
Introduction: Cognitive skills are essential in team sports. Perception, decision-making (tactical thinking, learning, attention, thinking, emotions), stress tolerance, and even the level of motor and technical-tactical skills all affect performance. Objective: We found a significant difference in stress tolerance of novice / young and experienced team sport players (BALOGH, DONKA 2020). Our results showed that experienced athletes have higher level of  stress tolerance.  However, as this was a descriptive study, we intended to support our statement involving more number of subjects, and an analysis of cognitive abilities. Method: A cross-sectional experimental study was performed on 41 male and 13 female team sport (handball, volleyball and football) players. We used the VTS DT software package for cognitive abilities and the MDE Heidelberg StressHolter (gastro, HR, TH, GSR) for stress measurement. During the 35-minute measurement process, a state of rest was measured in the first stage, a response to a 10-minute stress situation (VTS-DT for the cognitive test) in the second stage, and a state of rest and latency in the third stage. Results: We found a significant relationship between stress tolerance and the cognitive ability of female and male participants. Our results demonstrated that football players had a lower level of  stress tolerance than other team sport players. They also tent to make more mistakes in the VTS-DT test. Conclusions: The classification into novice and experienced categories need to be done more uniformly in the future. We are aware of it, that the unequal number of participants by sports, is one of the limitations of our study. However, it is encouraging that significant results demonstrate a strong relationship between stress tolerance and the number of appropriate decisions. These results reveal other areas of research for us.